Movement Coordination Learning Model: Basic Motoric Skill For Elementary Students - Anggi Setia Lengkana; Entan Saptani; Encep Sudirjo; Mia Rosalina; Dadang Budi Hermawan; Bambang Gatot Sugiarto (STKIP Muhammadiyah Kuningan, 2022)
This study aims to analyze the effect of the movement coordination learning model on the development of basic motor movements in elementary school-aged children. A total of 50 students became research subjects taken randomly from a total population of 83 people. This study uses an experimental model with